The Implementation of Politeness Strategy in a Group of Teenagers in Tambak District Banyumas Regency - Arif Nur Wahid, Wahid (Papanda Journal of English Education, 2025)
Abstract This study aims to examine the application of politeness strategies in the daily conversations of teenagers in their hangouts at their friend's house. This study use qualitative method. Language is not just for communication but also crucial for establishing and maintaining relationships in society. People use politeness strategies, such as those proposed by Brown and Levinson, to enhance communication harmony by focusing on maintaining "face," which is an individual's public self-image that should be respected during interactions.Politeness strategies help minimize Face Threatening Acts (FTA), which occur when actions go against the wishes of others, potentially damaging their face through non-verbal cues or expressions. The concept of politeness involves showing concern for positive and negative face needs, where positive face desires approval and respect, while negative face seeks freedom to act without hindrance. Linguists like Mouton, Lakoof, Watts, Holmes, emphasize the role of politeness in minimizing conflicts and showing concern for others' feelings. Keywords : Politeness, Brown & Levinson, Teenagers.